2021
DOI: 10.1007/s10404-021-02424-z
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly of coated microdroplets at the sudden expansion of a microchannel

Abstract: We report observations of the self-assembly of coated droplets into regular clusters at the sudden expansion of a microfluidic channel. A double emulsion consisting of a regular train of coated microdroplets was created upstream of the channel expansion, so that the inter-drop distance, droplet length, velocity and coating thickness could be varied by imposing different inlet pressures, albeit not independently. Provided that the enlarged channel remains sufficiently confined to prohibit propagation in double … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
(49 reference statements)
0
4
0
Order By: Relevance
“…In the microfluidic experiments, a suspension of silicone oil droplets (Sigma Aldrich, viscosity ν = 20 cSt with paraffin oil dye) in a mixture of water and glycerol (Sigma Aldrich, 80 : 20 by volume with 0.2% SDS, viscosity 0.24 Pa s at 21C) was used as biomimetic model for blood. The droplets were generated in a flow-focusing device [33] which was connected to the porous medium via a bent glass capillary (length 100 mm, outer diameter 1 mm, inner diameter 0.58 mm). Droplets with a diameter of 240 μm were produced by flowing the inner phase (silicone oil) at 4 μl min −1 and introducing the outer phase (water/glycerol) through a cross-junction at 5 μl min −1 immediately upstream of the flow-focusing channel constriction.…”
Section: Methodsmentioning
confidence: 99%
“…In the microfluidic experiments, a suspension of silicone oil droplets (Sigma Aldrich, viscosity ν = 20 cSt with paraffin oil dye) in a mixture of water and glycerol (Sigma Aldrich, 80 : 20 by volume with 0.2% SDS, viscosity 0.24 Pa s at 21C) was used as biomimetic model for blood. The droplets were generated in a flow-focusing device [33] which was connected to the porous medium via a bent glass capillary (length 100 mm, outer diameter 1 mm, inner diameter 0.58 mm). Droplets with a diameter of 240 μm were produced by flowing the inner phase (silicone oil) at 4 μl min −1 and introducing the outer phase (water/glycerol) through a cross-junction at 5 μl min −1 immediately upstream of the flow-focusing channel constriction.…”
Section: Methodsmentioning
confidence: 99%
“…In the microfluidic experiments, a suspension of silicone oil droplets (Sigma Aldrich, viscosity ν = 20 cSt with paraffin oil dye) in a mixture of water and glycerol (Sigma Aldrich, 80:20 by volume with 0.2% SDS, viscosity 0.24 Pa s at 21°C) is used as biomimetic model for blood. The droplets were generated in a flow-focusing device [29] which was connected to the porous medium via a bent glass capillary (length 100 mm, outer diameter 1 mm, inner diameter 0.58 mm). Droplets with a diameter of 240 μ m were produced by flowing the inner phase (silicone oil) at 4 μ L/min and introducing the outer phase (water/glycerol) through a cross-junction at 5 μ L/min immediately upstream of the flow-focusing channel constriction.…”
Section: Methodsmentioning
confidence: 99%
“…Most studies have focused on the equivalent of the experimentally observed solution branches: nearly circular drops, or smooth, half-width air fingers, each symmetric about the channel centre line and with no inflection points. Recent 3D studies for strongly confined drops [12,13] confirm that the films which confine the drops are not uniform in thickness. These thin films affect the drag on the drop [14][15][16][17] and have an important role in systems with surfactants as they dominate the surface area of the drop, and hence, any surface transport processes [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…[21]) no-penetration conditions but not no-slip are applied at channel side walls, while at the fluid interface, a pressure jump is enforced relating to surface tension, which is a large aspect ratio equivalent of the normal stress condition. The tangential stress condition is neglected entirely and in the extension to the two-fluid case continuity of tangential velocity can also not be applied, thus, neglecting some important coupling for two-fluid or Marangoni cases [13,19,22]. In the absence of surface tension, [1,2] showed that steady propagation in the Darcy model yields a continuum of solutions, for both bubbles, with fixed finite volume, or for semi-infinite air fingers.…”
Section: Introductionmentioning
confidence: 99%